Effectiveness of Exercise-Based Interventions on Molecular Biomarkers in Head and Neck Cancer (HNC) Survivors: A Systematic Review - Hritika D. Pai MPT; K Vijaya Kumar PhD; Prasanna Mithra MD, DNB; Shruti D’Souza MPT; Poornima Ajay Manjrekar MD, PhD; Stephen Rajan Samuel PhD; Justin W. L. Keogh PhD (Integrative Cancer Therapies)
Purpose: HNC poses significant health challenges globally with over 650 000 new cases annually. Studies have demonstrated the benefits of exercise for many cancer types, with several exploring the effects of exercise on various molecular biomarkers. However, no study has systematically explored these effects among HNC survivors. Methods: Studies published up to February 2024 were screened on PubMed, SCOPUS and Web of Science using relevant keywords yielding 838 results. Studies that explored the effect of exercise-based interventions on molecular biomarkers among HNC survivors were eligible for inclusion. Risk of bias was assessed using the Joanna Briggs Institute quality assessment tool. Results: Three studies were included in the review. Primary biomarkers assessed were inflammatory (eg, IL-6, TNF-α), oxidative stress (eg, 8-OHdG, MDA), and collagen fragment markers (eg, IC6, ProC3). Significant changes were observed in collagen fragment markers, specifically Pro C3, IC6 and IC6/C6M over time, although no correlation with lean body mass was found. Oxidative stress markers improved following exercise, with increases in total antioxidant capacity, decreases in 8-OHdG and carbonyl content. However, no significant changes were found in inflammatory markers or DNA methylation patterns post-intervention. Conclusion: Our review suggests that exercise shows potential in modulating physiological and molecular pathways’ among HNC survivors. Although only 3 studies were eligible for inclusion, these benefits might potentially translate into improvements in health-related outcomes amongst HNC survivors. Future large-scale trials with standardized exercise protocols and extended follow-up periods might improve our understanding of the long-term effects of exercise on biomarkers and survivorship outcomes in HNC. PROSPERO Registration Number: CRD42024508084